Effect of Quality Assurance Deficit on Market Competitiveness for Export Commodities and Household Income in Nigeria - Akanni , Kassim Adekunle (Applied Studies in Agribusiness and Commerce, 2018)
The Nigerian’s agricultural sub-sector contributes about 37 percent of her Gross Domestic Product (GDP) and employs about 65 per cent of the adult labour force. It is thus the major source of food and fibre for the nation. However, there are increasing concerns about the quality and level of safety of many of the agricultural export commodities, particularly in the European markets due to the composition of high level of unauthorized pesticides. This is a major challenge to the level of market competitiveness for these commodities in the international markets. This study therefore examined the effect of quality assurance deficit on market competitiveness and household income levels. Trends in Nigeria’s agricultural export trade between 1980 and 2014 were examined and emphasis was placed on cowpea, dried maize, melon seeds and palm oil. Descriptive and qualitative statistical methods were used to analyze the data. Quantitative statistics included the use of econometric models. Results indicated that there was an increase in the general price level of the commodities at the international market over time. The aggregate market demand for each of them dropped sharply in the last one decade even when the market price per unit increased steadily. This negatively affected the households’ average income level as returns on sales of export commodities declined. Huge quantities of the commodities were then forced to be sold at the local markets at cheaper prices. This development negatively affects the consumptions patterns of the exporters as they now have reduced disposable income. Appropriate agencies of government need to be awake to their responsibilities of assessing and certifying the quality of the Nigerian agricultural commodities before exporting them abroad. This will help to further boost the level of consumer confidence in these export commodities especially at the international markets.JEL Classification: Q13